Exploring the Contributions of Kashmir in the Dissemination and Development of Buddhist Thought across Asia - Kumar, Chandan (Dhammacakka Journal of Buddhism and Applied Buddhism, 2025)
Kashmir has long occupied a sacred and strategic position in the Buddhist world, serving as both a sanctum of advanced learning and a dynamic center for trans-regional transmission of doctrine, art, and literature. While modern scholarship has often focused on other celebrated sites such as Nalanda or Bodh Gaya, this article argues that the geographical dissemination of Buddhism was significantly shaped by the intellectual and spiritual endeavours emerging from Kashmir. Through its monastic institutions, scriptural commentaries, and far-reaching missionary networks, Kashmir not only preserved key tenets of Sarvāstivāda and Mahāyāna traditions but also transformed them into exportable paradigms for China, Central Asia, and Tibet. This paper reconstructs the expansive role played by Kashmir from the reign of King Kaniṣka to the early second millennium CE, highlighting the works of master translators such as Kumārajīva, Saṅghadeva, and Śākyasribhadra. Drawing upon historical narratives, epigraphical sources, and cross-cultural testimonies from the Chinese Tripiṭaka, Tibetan annals, and Central Asian chronicles, the study demonstrates that Kashmir was not merely a transmitter but a generative source of Buddhist innovation, exegesis, and aesthetics.